1986
DOI: 10.1084/jem.163.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Glucose induces intracisternal type A retroviral gene transcription and translation in pancreatic beta cells.

Abstract: In a study (1) analyzing the response of different inbred strains of mice to the autosomal recessive obesity mutation, "diabetes" (db), we found that only those inbred strains constitutively expressing in beta cells an endogenous retrovirus, the intracisternal type A particle (IAP), 1 developed severe diabetes. The beta cell was the only islet endocrine cell type observed to express IAP; cell necrosis was limited to this cell type as well. In chronically hyperglycemic db/db mice, prenecrotic beta cells showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Moreover, male mice of the BKs strain are particularly sensitive to diabetes induced by multiple low-dose streptozotocin administration, whereas B6 mice are more resistant to this mode of treatment (25). The two strains also exhibit different expressions of endogenous retroviral genes in response to high glucose (26), and BKs mice but not B6 mice spontaneously produce islet autoantibodies (27). Previous experiments with transplanted islets have also demonstrated that islet cells have a higher regeneratory capacity in B6 mice than in BKs mice (28).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, male mice of the BKs strain are particularly sensitive to diabetes induced by multiple low-dose streptozotocin administration, whereas B6 mice are more resistant to this mode of treatment (25). The two strains also exhibit different expressions of endogenous retroviral genes in response to high glucose (26), and BKs mice but not B6 mice spontaneously produce islet autoantibodies (27). Previous experiments with transplanted islets have also demonstrated that islet cells have a higher regeneratory capacity in B6 mice than in BKs mice (28).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes pathogenesis in BKS-Lepr db-1J mice was particularly responsive to dietary carbohydrate (19). Elevated glucose concentrations in vitro induced expression of defective endogenous retroviral genomes in ␤-cells from wild-type BKS but not B6 islets (20). Male BKS mice were further differentiated from B6 males in terms of their heightened sensitivity to diabetes induced by diabetogens, including alloxan (21) and multiple low doses of streptozotocin (22).…”
Section: C57blks/j and Nod/lt: Two Paradigm Diabetes-permissive Inbrementioning
confidence: 99%
“…During early embryogenesis, IAP transcripts can be detected in embryos from the first cleavage to blastocysts (46,56); in adult mice, IAP transcripts can be detected at significant levels in several somatic tissues (15,32; reviewed in reference 30), with highest expression in the cortical thymocytes (but still Ͻ5% of that in myeloma cells). This expression, however, varies among different mouse strains, and in several instances IAP proteins or particles could not be detected by using immunological approaches (32,34) or electron microscopy (53). The biological relevance of these transcripts, therefore, can be questioned.…”
mentioning
confidence: 99%